Design for disassembly in electric rice cooker manufacturing - Cheng, Siew Min; Raja Mamat, Tengku Nur Azila (Progress in Engineering Application and Technology, 2021)
Most of the broken or damaged electric rice cooker will be simply dumped as e-waste without planning for repair or reuse due to its complexity. Hence, the main objective of this research is to propose the design for disassembly in electric rice cooker manufacturing for easy disassembly without the assistance of tooling so that components can be repaired, reused or recycled. In order to achieve the objectives of the study, a questionnaire survey was carried out to determine the part that most easily broken in the electric rice cooker from respondents. Based on the survey results, the redesign will be focused on the mechanical part of the electric rice cooker which is the part that most easily broken so that it can be access and disassemble in shorter time. In this research, two designs were proposed which are Design A and Design B. Then, the mechanical properties of proposed electric rice cooker were analysed using simulation in SolidWorks software. Finite Element Analysis (FEA) will be run in this research which are stress and thermal analysis to predict how the existing and proposed electric rice cooker reacts to forces, heat and other physical effects. After FEA was completed, Design for Manufacturing and Assembly (DFMA) analysis was applied to compare the cost and the design efficiency of the existing and proposed electric rice cooker. From the result obtained, Design B which was applied circular pattern snap fit mechanism to replace the screw as the fasteners had been chosen as the best design. Design B has the highest DFA index which the value is 84.10 and lowest manufacturing cost which is $63.41.